Threaded intramedullary headless nail fixation for fractures requiring carpometacarpal stabilization. (March 2023) - Baum, Gracie R.; Dang, Michael; Yeater, Thomas B.; Brown, Elizabeth; Cox, Cameron T.; Bourland, Bryan; MacKay, Brendan J.
Abstract: Carpometacarpal (CMC) fracture-dislocations are uncommon hand injuries, with few studies available regarding their treatment. The current operative treatment options include fixation with K-wires, mini-screws, or plates, though there is no standardized approach because of varying injury patterns and complications associated with each device. The INnate™ threaded intramedullary nail is a relatively novel treatment option that has shown promise in metacarpal fracture fixation by facilitating faster mobilization and recovery with enhanced rotational stability and no compression to prevent fracture displacement and shortening. This study assesses the efficacy of the INnate™ nail for fixation of CMC fracture-dislocations of the second through fifth joints. Nine patients with fourteen CMC fracture-dislocations treated with the INnate™ nail at the University Medical Center between 2019 and 2021 were enrolled in the study. We evaluated postoperative outcomes in terms of pain, total active range of motion (TAM), and return to normal activities. Of the nine patients, seven returned for follow-up. The average time to radiographic union was 11.5 weeks. At final follow-up, no patient reported pain ( n = 6). Four patients had 100% TAM, 1 had 95% TAM, and 1 had 25% TAM. The average percentage of normal activity resumed was 84.0% ( n = 5). No significant complications were reported. One patient had a dorsal spanning plate; hence, we were unable to record outcomes measures regarding the CMC injury. An additional patient had diminished ROM of the injured hand, but his last follow-up was only 1 month postop. Our pilot data overall suggest that the INnate™ threaded intramedullary nail has the potential to improve treatment algorithms for CMC fracture-dislocations.